Peningkatan Hasil Belajar Melalui Penggunaan Metode Diskusi di Kelas V Semester II SDN 03 Talang Maua Kecamatan Mungka - Ewidarti, Ewidarti (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2018)
This research was motivated by the low learning outcomes of the students of SDN 03 Talang Maua. Among the contributing factors is the inappropriate delivery of material and inappropriate methods so that students are bored and not interested in this learning. Other consequences students are not brave and lazy when completing tasks and learning outcomes are low. One of the right ways is to use the Discussion method. The purpose of this study is to improve student learning outcomes in science learning through the use of discussion methods in class V semester II SDN 03 Talang Maua. This type of research is Classroom Action Research (CAR). The subjects of this study were students of class V SDN 03 Talang Maua. Based on the results of the study showed that the average learning outcomes in the first cycle was 63.47% and the average learning outcomes in the second cycle was 74.13%. This means that the learning outcomes of Natural Sciences through the use of the discussion method at SDN 03 Talang Maua increased compared to the learning outcomes of Cycle 1 with cycle 2.